Etika Cyber Qur'ani di Era Society 5.0: Integrasi Amanah dan Tabayyun Digital sebagai Kerangka Preventif Krisis Privasi - Siti Asiah; Dinda Salsabila Adzro Junaidi (Lembaga Bale Literasi, 2025)
This study aims to construct Qur'anic Cyber Ethics in the era of Society 5.0 as a preventive framework against the privacy crisis triggered by widespread data breaches and digital information misuse in Indonesia. Indonesia ranks among Southeast Asian countries with the highest data leakage rates, with approximately 156.8 million digital user accounts compromised between 2004 and 2024. This phenomenon reflects not only a technological problem but also an ethical and moral one, requiring a value-based response that complements existing techno-legal approaches. The method used is a qualitative descriptive approach with thematic Qur'anic textual analysis (mawdu'i), supported by document analysis of empirical data on data breach cases in Indonesia. The data sources consist of Qur'anic verses on amanah (QS. Al-Ahzab: 72) and tabayyun (QS. Al-Hujurat: 6), classical and contemporary tafsir works including Tafsir Al-Azhar, Tafsir Al-Mishbah, and Fi Zilal Al-Qur'an, alongside contemporary studies on digital privacy. The results of the study show that Qur'anic Cyber Ethics integrates two core principles: Digital Amanah, defined as the responsibility to safeguard data, identity, and trust; and Digital Tabayyun, understood as the obligation to verify and clarify information before dissemination. The novelty of this study lies in operationalizing these principles through the formation of a DATE community (Digital Amanah and Tabayyun Ethics) and three actionable guidelines: making digital amanah a personal identity, applying digital tabayyun before sharing, and reviving Qur'anic digital education. As the main contribution, this framework offers a faith-based ethical alternative that strengthens existing legal and technical approaches to addressing the privacy crisis, particularly in Muslim-majority societies undergoing rapid digital transformation.